Assessing Reliability of Criterion-Referenced Instruments - Robertson, Gary J. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
Some fundamental concepts of criterion referenced test (CRT) reliability are highlighted. Emphasis is given to the procedures for determining reliability of scores for individual pupils because this is an area requiring increased awareness by classroom teachers and practitioners. Reliability issues encountered in the evaluation of instructional programs are not considered, however. After some preliminary remarks about reliability, methods of estimating CRT reliability are discussed as are additional considerations affecting CRT reliability estimates. (Author/GK)
ERIC Note: Paper presented at the Annual Meeting of the International Reading Association (26th, New Orleans, LA, April 30, 1981).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Criterion Referenced Tests; Reading Tests; Scores; Test Reliability; Domain Referenced Tests -- Reliability Formulas; Estimation; Speeches/Meeting Papers; Opinion Papers